Microbiological, Physicochemical and Starch Digestability Properties of Spontaneous Fermented Sorghum Flour - Pranoto, Yudi (2010)
Sorghum is an underutilized food source in Indonesia which is potential to be developed for foodstuff. It is easily grown and containing significant nutritional components, such as carbohydrate and protein. For human consumption, sorghum contains antinutritional factor like tannin and phytacte, which lead to low starch and protein digestability value and possessing unfavorable taste. Fermentation has been reported to improve nutritional value of the sorghum by increasing soluble protein and decreasing tannin. However, the effect of fermentation on the starch digestability is rarely reported. This work aimed to study effect of the spontaneous fermentation in sorghum flour on the microbiological, physiochemical and starch digestability properties. Amount of 100 g sorghum flour was added with 200 ml of sterile distilled water in erlenmeyer flask, and incubated at 37oC for 24 h. Lactic acid bacteria, total aerobic bacteria, pH, and total acid were analyzed every 4 h during fermentation. For analyses of starch digestability (in vitro) and pasting properties, the samples were firstly dried at 60oC to attain moisture content of 10%. The results showed that the initial number of lactic acid bacteria and aerobic bacteria was similar. During fermentation, aerobic bacteria declined and lactic acid increased. The pH of the fermenting medium decreased and the total acid increased concurrently throughout fermentation. Starch digestability raised from 36.25% to 60%. There was a decrease in gelatinization temperature of the fermented sorghum flour from 87.6 oC to 86.2 oC along with the increased pasting viscosity from 716 cP to 761 cP. It can be concluded that sorghum is also potential for foodstuff as carbohydrate source.